Dielectric slurry for multilayer ceramic capacitor and preparation method thereof

By adding barium titanate and metal oxide to barium feldspar-based ceramic powder, the composition of the dielectric slurry is optimized, and the problem of insufficient dielectric constant and stability of the barium feldspar-based multi-layer ceramic capacitor is solved, thereby achieving efficient improvement of electrical performance and improvement of slurry moldability.

CN119694786APending Publication Date: 2025-03-25LIAONING SILICATE RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411839103.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In practical applications, barium feldspar multi-layer ceramic capacitors face problems such as insufficient temperature and frequency stability of the dielectric constant and insufficient rheology and moldability of the dielectric slurry, which affects the reliability and production accuracy of the capacitor.

Method used

By adding barium titanate, metal oxide and other components to barium feldspar-based ceramic powder, the synergistic effect between these components is used to optimize the composition of the medium slurry and improve its electrical properties. Specific steps include ball milling, drying, pre-sintering, casting and high-temperature sintering.

Benefits of technology

A ceramic capacitor dielectric material sintered in the temperature range of 1000 to 1200°C is realized, which improves the dielectric constant, reduces losses, enhances the temperature stability of the material and resists electric field breakdown, and improves the rheology and moldability of the slurry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses dielectric slurry for a multilayer ceramic capacitor and a preparation method of the dielectric slurry, and the dielectric slurry comprises the following components in percentage by weight: 12%-18% of a solvent, 0.15%-0.3% of a dispersing agent, 0.05%-0.1% of a plasticizer, 17%-22% of a binder, 0.01%-0.05% of a defoaming agent and the balance of composite ceramic powder. By adding barium titanate and niobium oxide, the dielectric constant can be increased, the polarization characteristic of the material can be improved, and the polarization effect can be increased; the oxides of aluminum and zinc can improve the thermal stability of the ceramic and prevent defects from forming in the sintering process; magnesium, nickel and other oxides promote sintering, improve the density of a ceramic matrix, improve the thermal stability of the material and enhance the electric field breakdown resistance of the material. By adopting the formula and the preparation method disclosed by the invention, a celsian-based ceramic capacitor product with excellent dielectric property, high stability and relatively low loss can be obtained, and the method is suitable for preparing a multilayer ceramic capacitor with high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of celsium feldspar-based ceramic capacitors, in particular to a dielectric slurry for multilayer ceramic capacitors and a preparation method thereof. Background Art

[0002] As one of the representatives of ceramic electronic components, multilayer ceramic capacitors (MLCC) have been widely used in various electronic devices in the information, military, mobile communications, electronic appliances, aviation, oil exploration and other industries due to their advantages such as small size, low price, compact structure and large capacity. With the increasing market demand for high-reliability and high-performance multilayer ceramic capacitors, barium feldspar, as a potential ceramic material, has gradually become a research hotspot. In recent years, barium feldspar-based dielectric materials have shown good prospects in improving dielectric constant, temperature stability and reducing losses. At the same time, the application of barium feldspar can reduce the use of heavy metals and organic solvents, and will become an important direction for green manufacturing.

[0003] Although the research on barium feldspar-based multilayer ceramic capacitors has made some progress, there are still many technical challenges in practical applications. First, the temperature and frequency stability of the dielectric constant is insufficient, which affects the reliability of the capacitor. Second, the rheology and formability of the existing dielectric slurry formula are insufficient, which limits the realization of high-precision production. These problems urgently need to be improved by optimizing the slurry composition and doping technology. Summary of the invention

[0004] The present invention aims to provide a temperature-stable barium feldspar multilayer ceramic capacitor dielectric material. The dielectric material is based on barium feldspar, and by adding components to barium feldspar-based ceramic powder and utilizing the synergistic effect between the added components, the composition of the barium feldspar-based ceramic dielectric slurry is optimized to improve its electrical properties.

[0005] To achieve the above object, the present invention adopts the following specific technical solutions:

[0006] A dielectric slurry for multilayer ceramic capacitors consists of the following components by weight: 12% to 18% solvent, 0.15% to 0.3% dispersant, 0.05% to 0.1% plasticizer, 17% to 22% binder, 0.01% to 0.05% defoamer and the remainder of composite ceramic powder.

[0007] Furthermore, the composite ceramic powder is composed of 80% by mole of balsamite ceramic powder, 8% to 15% of barium titanate, and 5% to 12% of metal oxide.

[0008] Furthermore, the metal oxide is one or more of niobium oxide, aluminum oxide, zinc oxide, magnesium oxide and nickel oxide.

[0009] Furthermore, the solvent is a mixed solvent of xylene and ethanol, or toluene and ethanol.

[0010] Furthermore, the dispersant is a modified ammonium salt dispersant.

[0011] Furthermore, the plasticizer is one of dioctyl o-carboxylate, triphenyl phosphate, and cyclohexyl diphenyl phosphate.

[0012] Furthermore, the defoamer is a modified polyether defoamer.

[0013] A method for preparing a dielectric slurry for a multilayer ceramic capacitor, wherein the dielectric slurry is composed of the following components by mass percentage: 12% to 18% solvent, 0.15% to 0.3% dispersant, 0.05% to 0.1% plasticizer, 17% to 22% binder, 0.01% to 0.05% defoamer and the remainder of composite ceramic powder. The steps of preparing the dielectric slurry include:

[0014] Step 1, primary ball milling: weighing composite ceramic raw material powder, anhydrous ethanol and ball milling medium, mixing, and ball milling to obtain primary ball milled powder; the composite ceramic raw material powder is composed of the following components by mole percentage: 80% of celsium feldspar ceramic powder, 8% to 15% of barium titanate, and 5% to 12% of metal oxide;

[0015] Step 2, drying and sieving: drying and sieving the first ball-milled powder;

[0016] Step 3, pre-sintering: pre-sintering the dried and sieved powder to obtain pre-sintered powder; the pre-sintering temperature is 1200-1400°C, the pre-sintering time is 2-4h, and the pre-sintering temperature rise and fall gradient is 5-10°C / min;

[0017] Step 4, secondary ball milling: mixing the pre-burned powder, anhydrous ethanol and ball milling medium, and ball milling to obtain secondary ball milled powder, and drying and sieving the secondary ball milled powder to finally obtain composite ceramic powder;

[0018] Step 5, weigh the composite ceramic powder, solvent and dispersant in the medium slurry into a ball mill and ball mill at a speed of 50 to 300 rpm for 2 to 4 hours to mix them evenly;

[0019] Step 6: Add the remaining components in the medium slurry into the ball milling tank, and continue to ball mill under the ball milling conditions in step 5 to obtain a tape casting slurry;

[0020] Step 7: Apply the ceramic slurry onto the membrane belt through the casting device to form a uniform slurry layer on the membrane belt, and form a ceramic membrane after drying;

[0021] Step eight, stacking the ceramic diaphragms to form a block;

[0022] Step nine, isothermally pressing the block at 15Mpa to 30Mpa to obtain a ceramic body of corresponding shape and size;

[0023] Step 10: Debinding and high-temperature sintering the ceramic body.

[0024] Furthermore, in step one and step three, the mass ratio of the raw material powder, anhydrous ethanol, and zirconium oxide balls is 1:1.5-2:1-1.5; the diameter of the zirconium oxide balls is 1-10 mm; the ball milling speed is 300-600 rpm, and the ball milling time is 20-24 h; the drying temperature of the first ball milled powder or the second ball milled powder is 60-80°C, and the drying time is 3-6 h.

[0025] Furthermore, in step ten, the debinding temperature is 150°C to 650°C, and the debinding holding time is 3 to 6 hours; the sintering temperature is 1000°C to 1200°C, the sintering temperature ramp is 2 to 5°C / min, and the sintering holding time is 1 to 3 hours.

[0026] The present invention can achieve the following technical effects:

[0027] The present invention obtains a ceramic capacitor dielectric material that can be sintered within a temperature range of 1000 to 1200° C. by regulating the proportion of different added components. The barium feldspar multilayer ceramic capacitor dielectric material is mainly barium feldspar, accounting for 80wt% of the total dielectric material; by adding components to the barium feldspar-based ceramic powder, the synergistic effect between the added components is utilized to optimize the composition of the barium feldspar-based ceramic dielectric slurry and improve its electrical properties. By adding components, the grain boundary thickness is increased and the ferroelectric phase is diluted, effectively improving the capacitance of the capacitor; adjusting the shape, size and distribution of the constituent phases to improve the insulation performance of the ceramic matrix; promoting sintering, effectively improving the density of the ceramic matrix, thereby improving the electrical performance of the device, and improving the shortcomings of the slurry rheology and formability. In the above-mentioned ceramic slurry, the addition of barium titanate and niobium oxides can improve the dielectric constant, improve the polarization characteristics of the material, and help increase the polarization effect; aluminum and zinc oxides can improve the thermal stability of the ceramic and prevent the formation of defects during the sintering process; magnesium, nickel and other oxides promote sintering to increase the density of the ceramic matrix, improve the thermal stability of the material, and enhance the material's ability to resist electric field breakdown.

[0028] The process is simple, the raw materials for the formula are widely available, the cost is low and simple to control, and the sintering conditions are simple. The prepared ceramic slurry can improve the dielectric constant of barium feldspar-based ceramic capacitors, reduce losses, improve stability, and reduce the content of precious metals in the internal electrodes, thereby reducing costs. The dielectric material properties of the resulting temperature-stable barium feldspar-based multilayer ceramic capacitor can meet the following indicators: the grain size of the ceramic dielectric slurry can be controlled within 100-600nm, the thickness of the ceramic dielectric film is between 100 and 150μm, and the temperature variation rate (TCC) is within the range of ±5% within the temperature range of -55°C to +125°C, the room temperature dielectric constant ranges from 50 to 150, and the room temperature dielectric loss is ≤0.35%. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and do not constitute a limitation of the present invention.

[0030] A dielectric slurry for multilayer ceramic capacitors consists of the following components by weight: 12% to 18% solvent, 0.15% to 0.3% dispersant, 0.05% to 0.1% plasticizer, 17% to 22% binder, 0.01% to 0.05% defoamer and the remainder of composite ceramic powder.

[0031] Furthermore, the composite ceramic powder is composed of balsamite ceramic powder, 8% to 15% of barium titanate, and 5% to 12% by mole of metal oxide.

[0032] Furthermore, the metal oxide is one or more of niobium oxide, aluminum oxide, zinc oxide, magnesium oxide and nickel oxide.

[0033] Furthermore, the solvent is a mixed solvent of xylene and ethanol, or toluene and ethanol.

[0034] Furthermore, the dispersant is a modified ammonium salt dispersant.

[0035] Furthermore, the plasticizer is one of dioctyl o-carboxylate, triphenyl phosphate, and cyclohexyl diphenyl phosphate.

[0036] Furthermore, the defoamer is a modified polyether defoamer.

[0037] The adhesive is a commonly used adhesive in the art, such as at least one of polyvinyl butyral (PVB), polyvinyl alcohol (PVA), polyacrylate (PAA) and polyurethane (PU).

[0038] A method for preparing a dielectric slurry for a multilayer ceramic capacitor, comprising:

[0039] Step 1, primary ball milling: the composite ceramic raw material powder, anhydrous ethanol and ball milling medium weighed in proportion are mixed and ball milled to obtain a primary ball milled powder; the composite ceramic raw material powder is composed of the following components by mole percentage: 80% of celsium feldspar ceramic powder, 8% to 15% of barium titanate and 5% to 12% of metal oxide;

[0040] Step 2, drying and sieving: drying and sieving the first ball-milled powder;

[0041] Step 3: pre-burning: pre-burning the dried and sieved powder to obtain pre-burned powder;

[0042] Step 4: Secondary ball milling: the pre-sintered powder is mixed with the ball milling medium, and ball milled to obtain secondary ball milled powder. The secondary ball milled powder is dried and sieved to finally obtain composite ceramic powder.

[0043] Step 5, weighing the composite ceramic powder, solvent, and dispersant into a ball mill and ball milling at a speed of 50 to 300 rpm for 2 to 4 hours to mix them evenly;

[0044] Step 6: Add the remaining components in the formula into the ball mill, and continue to ball mill under the ball milling conditions in step 5 to obtain the tape casting slurry.

[0045] Step 7: Apply the ceramic slurry onto the membrane belt through the casting device to form a uniform slurry layer on the membrane belt, and form a ceramic membrane after drying;

[0046] Step 8: stacking the ceramic diaphragms to form a block;

[0047] Step nine, isothermally pressing the block at 15Mpa to 30Mpa to obtain a ceramic body of corresponding shape and size;

[0048] Step 10: Debinding and high-temperature sintering the ceramic body.

[0049] Furthermore, in step one or step three, the mass ratio of the raw material powder, anhydrous ethanol, and zirconium oxide balls is 1:1.5-2:1-1.5; the diameter of the zirconium oxide balls is 1-10 mm; the ball milling speed is 300-600 rpm, and the ball milling time is 20-24 h; the drying temperature of the first ball milled powder or the second ball milled powder is 60-80°C, and the drying time is 3-6 h.

[0050] Preferably, in step three, the pre-sintering temperature is 1200-1400° C., the pre-sintering time is 2-4 hours, and the pre-sintering temperature rise and fall gradient is 5-10° C. / min.

[0051] Preferably, the casting rate used in step seven is 20-40 cm / min, and the scraper height is 120-300 μm;

[0052] Preferably, in step ten, the binder removal temperature is 150°C to 650°C, and the binder removal insulation time is 3 to 6 hours; the sintering temperature is 1000°C to 1200°C, the sintering temperature ramp is 2 to 5°C / min, and the sintering insulation time is 1 to 3 hours.

[0053] Example 1:

[0054] Formula composition (by weight): 16.18% solvent, 0.25% dispersant, 0.06% plasticizer, 21.50% binder, 0.01% defoamer and 62.00% composite ceramic powder (see Table 1 for specific proportions). The composite ceramic powder includes: in molar percentage, 80% barium feldspar powder, 12% barium titanate, 1% niobium oxide, 2% aluminum oxide, 2% zinc oxide, 2% magnesium oxide, and 1% nickel oxide. The composite ceramic raw material powder weighed in proportion is ball-milled, dried, sieved and pre-fired to obtain the composite ceramic powder; the weighed composite ceramic powder, solvent and dispersant are placed in a ball mill and ball-milled for 2 to 4 hours to mix them evenly; the remaining components in the formula are added to the ball mill, and the ball milling is continued under the ball milling conditions described above to obtain the tape casting slurry. The ceramic slurry was passed through a casting device to obtain a ceramic diaphragm; the ceramic diaphragm was subjected to processes such as lamination, isothermal static pressing, debinding and high-temperature sintering to obtain a circular ceramic sample for testing. The test results are shown in Table 3.

[0055] Example 2:

[0056] Formula composition (by weight): 15.18% solvent, 0.25% dispersant, 0.06% plasticizer, 20.50% binder, 0.01% defoamer and 64% composite ceramic powder (see Table 1 for specific proportions). Composite ceramic powder includes: 80% barium feldspar powder, 10% barium titanate, 2% niobium oxide, 3% aluminum oxide, 2% zinc oxide, 2% magnesium oxide, 1% nickel oxide in molar percentage. The composite ceramic raw material powder weighed in proportion is ball-milled, dried, sieved and pre-sintered to obtain composite ceramic powder; the weighed composite ceramic powder, solvent and dispersant are placed in a ball mill and ball-milled for 2 to 4 hours to mix them evenly; the remaining components in the formula are added to the ball mill and continue to be ball-milled under the previously described ball milling conditions to obtain a tape casting slurry. The ceramic slurry was passed through a casting device to obtain a ceramic diaphragm; the ceramic diaphragm was subjected to processes such as lamination, isothermal static pressing, debinding and high-temperature sintering to obtain a circular ceramic sample for testing. The test results are shown in Table 3.

[0057] Example 3:

[0058] Formula composition (by weight): 14.18% solvent, 0.25% dispersant, 0.06% plasticizer, 19.50% binder, 0.01% defoamer and 66% composite ceramic powder (see Table 1 for specific proportions). The composite ceramic powder includes: 80% barium feldspar powder, 10% barium titanate, 3% niobium oxide, 3% aluminum oxide, 2% zinc oxide, 1% magnesium oxide, and 1% nickel oxide in molar percentage. The composite ceramic raw material powder weighed in proportion is ball-milled, dried, sieved and pre-fired to obtain the composite ceramic powder; the weighed composite ceramic powder, solvent and dispersant are placed in a ball mill and ball-milled for 2 to 4 hours to mix them evenly; the remaining components in the formula are added to the ball mill, and the ball milling is continued under the ball milling conditions described above to obtain the tape casting slurry. The ceramic slurry was passed through a casting device to obtain a ceramic diaphragm; the ceramic diaphragm was subjected to processes such as lamination, isothermal static pressing, debinding and high-temperature sintering to obtain a circular ceramic sample for testing. The test results are shown in Table 3.

[0059] Example 4:

[0060] Formula composition (by weight): 13.18% solvent, 0.25% dispersant, 0.06% plasticizer, 18.50% binder, 0.01% defoamer and 68% composite ceramic powder (see Table 1 for specific proportions). Composite ceramic powder includes: 80% barium feldspar powder, 9% barium titanate, 3% niobium oxide, 3% aluminum oxide, 2% zinc oxide, 2% magnesium oxide, 1% nickel oxide in molar percentage. The composite ceramic raw material powder weighed in proportion is ball-milled, dried, sieved and pre-fired to obtain composite ceramic powder; the weighed composite ceramic powder, solvent and dispersant are placed in a ball mill and ball-milled for 2 to 4 hours to mix them evenly; the remaining components in the formula are added to the ball mill and continue to be ball-milled under the previously described ball milling conditions to obtain a tape casting slurry. The ceramic slurry is passed through the casting equipment to obtain the ceramic diaphragm; the ceramic diaphragm is stacked to form a block; then isothermal static pressing, debinding and high-temperature sintering are carried out to finally obtain a circular ceramic sample for testing. The test results are shown in Table 3. The ceramic slurry is passed through the casting equipment to obtain the ceramic diaphragm; the ceramic diaphragm is stacked, isothermal static pressing, debinding and high-temperature sintering to obtain a circular ceramic sample for testing. The test results are shown in Table 3.

[0061] Example 5:

[0062] Formula composition (by weight): 12.18% solvent, 0.25% dispersant, 0.06% plasticizer, 17.50% binder, 0.01% defoamer and 70% composite ceramic powder (see Table 1 for specific proportions). The composite ceramic powder includes: in molar percentage, 80% barium feldspar powder, 9% barium titanate, 2% niobium oxide, 4% aluminum oxide, 2% zinc oxide, 2% magnesium oxide, and 1% nickel oxide. The composite ceramic raw material powder weighed in proportion is ball-milled, dried, sieved and pre-fired to obtain the composite ceramic powder; the weighed composite ceramic powder, solvent and dispersant are placed in a ball mill and ball-milled for 2 to 4 hours to mix them evenly; the remaining components in the formula are added to the ball mill, and the ball milling is continued under the ball milling conditions described above to obtain the tape casting slurry. The ceramic slurry was passed through a casting device to obtain a ceramic diaphragm; the ceramic diaphragm was subjected to processes such as lamination, isothermal static pressing, debinding and high-temperature sintering to obtain a circular ceramic sample for testing. The test results are shown in Table 3.

[0063] The ceramic slurry of each example was prepared according to the method provided in the above implementation scheme, and its specific composition is shown in Table 1 and Table 2.

[0064] The composition of the ceramic composite powder is shown in Table 1.

[0065] Table 1: Mole percentage

[0066]

[0067] Ceramic slurry composition

[0068] Table 2: Mass percentage

[0069]

[0070] The performance of the ceramic capacitors prepared according to the slurry ratio of the composite ceramic powder embodiments 1 to 5 was tested, as shown in Table 3.

[0071] Table 3:

[0072]

[0073]

[0074] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0075] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention.

[0076] The above specific implementations of the present invention do not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A dielectric slurry for a multilayer ceramic capacitor, characterized in that: The invention is composed of the following components by weight percentage: 12% to 18% of solvent, 0.15% to 0.3% of dispersant, 0.05% to 0.1% of plasticizer, 17% to 22% of binder, 0.01% to 0.05% of defoamer and the remainder of composite ceramic powder.

2. The dielectric slurry for a multilayer ceramic capacitor according to claim 1, characterized in that: The composite ceramic powder consists of 80% by mole of balsam ceramic powder, 8% to 15% of barium titanate and 5% to 12% of metal oxide.

3. The dielectric slurry for a multilayer ceramic capacitor according to claim 1, characterized in that: The metal oxide is one or more of niobium oxide, aluminum oxide, zinc oxide, magnesium oxide and nickel oxide.

4. The dielectric slurry for a multilayer ceramic capacitor according to claim 1, characterized in that: The solvent is a mixed solvent of xylene and ethanol or toluene and ethanol.

5. The dielectric slurry for a multilayer ceramic capacitor according to claim 1, characterized in that: The dispersant is a modified ammonium salt dispersant.

6. The dielectric slurry for a multilayer ceramic capacitor according to claim 1, characterized in that: The plasticizer is one of dioctyl o-carboxylate, triphenyl phosphate and cyclohexyl diphenyl phosphate.

7. The dielectric slurry for a multilayer ceramic capacitor according to claim 1, characterized in that: The defoamer is a modified polyether defoamer.

8. The method for preparing a dielectric slurry for a multilayer ceramic capacitor according to any one of claims 1 to 7, characterized in that: The medium slurry is composed of the following components by mass percentage: 12% to 18% solvent, 0.15% to 0.3% dispersant, 0.05% to 0.1% plasticizer, 17% to 22% binder, 0.01% to 0.05% defoamer and the remainder of composite ceramic powder. The steps of preparing the medium slurry include: Step 1, primary ball milling: weighing composite ceramic raw material powder, anhydrous ethanol and ball milling medium, mixing, and ball milling to obtain primary ball milled powder; the composite ceramic raw material powder is composed of the following components by mole percentage: 80% of celsium feldspar ceramic powder, 8% to 15% of barium titanate, and 5% to 12% of metal oxide; Step 2, drying and sieving: drying and sieving the first ball-milled powder; Step 3, pre-sintering: pre-sintering the dried and sieved powder to obtain pre-sintered powder; the pre-sintering temperature is 1200-1400°C, the pre-sintering time is 2-4h, and the pre-sintering temperature rise and fall gradient is 5-10°C / min; Step 4, secondary ball milling: mixing the pre-burned powder, anhydrous ethanol and ball milling medium, and ball milling to obtain secondary ball milled powder, and drying and sieving the secondary ball milled powder to finally obtain composite ceramic powder; Step 5, weigh the composite ceramic powder, solvent and dispersant in the medium slurry into a ball mill and ball mill at a speed of 50 to 300 rpm for 2 to 4 hours to mix them evenly; Step 6: Add the remaining components in the medium slurry into the ball milling tank, and continue to ball mill under the ball milling conditions in step 5 to obtain a tape casting slurry; Step 7: Apply the ceramic slurry onto the membrane belt through the casting device to form a uniform slurry layer on the membrane belt, and form a ceramic membrane after drying; Step eight, stacking the ceramic diaphragms to form a block; Step nine, isothermally pressing the block at 15Mpa to 30Mpa to obtain a ceramic body of corresponding shape and size; Step 10: Debinding and high-temperature sintering the ceramic body.

9. The method for preparing a dielectric slurry for a multilayer ceramic capacitor according to claim 8, characterized in that: In the steps 1 and 3, the mass ratio of the raw material powder, anhydrous ethanol and zirconium oxide balls is 1:1.5-2:1-1.5; the diameter of the zirconium oxide balls is 1-10 mm; the ball milling speed is 300-600 rpm, and the ball milling time is 20-24 h; the drying temperature of the first ball milling powder or the second ball milling powder is 60-80° C., and the drying time is 3-6 h.

10. The method for preparing a dielectric slurry for a multilayer ceramic capacitor according to claim 8, characterized in that: In the step 10, the debinding temperature is 150°C to 650°C, and the debinding insulation time is 3 to 6 hours; the sintering temperature is 1000°C to 1200°C, the sintering temperature ramp is 2 to 5°C / min, and the sintering insulation time is 1 to 3 hours.